Factors Affecting the Stress Level of Students of the Faculty of Medicine, Muslim University of Indonesia in the Cardiovascular Block Practical Exam, Class of 2024 - Nur Qadri Wahid; Nurfachanti Fattah; Ilma Khaerina Amaliyah Bakhtiar; Muhammad Alim Jaya; Muhammad Wirasto Ismail (Rumah Sakit Ibnu Sina, Makassar, 2026)
Academic stress is often experienced by medical students due to the high demands of education, including practicum exams that assess psychomotor competence. This study aims to analyze the factors that affect the stress level of students of the Faculty of Medicine, Muslim University of Indonesia class of 2024 in facing the cardiovascular block practicum exam. This observational quantitative analytical research with a cross-sectional design involves all students of the class of 2024 as many as 230 respondents through a total sampling technique. Data collection was conducted using questionnaires of respondent characteristics and DASS 42, analyzed by Chi-Square test (p<0.05). The results showed that the majority of respondents were 19 years old (66.1%) and female (76.5%). Most students experienced moderate stress (40.4%). Bivariate analysis found that length of learning (p=0.001) and hours of sleep (p=0.001) were significantly related to the degree of stress, while age and gender were not related. It was concluded that academic and environmental factors play a role in student stress, so intervention is needed to balance study time and rest.